2019
DOI: 10.1108/ccsm-02-2018-0028
|View full text |Cite
|
Sign up to set email alerts
|

Host country experience, institutional distance and location choice of Chinese MNEs

Abstract: Purpose The conventional wisdom suggests that the lack of prior host country-specific experience and a higher institutional distance deter multinational enterprises (MNEs) from entering a foreign country. However, past studies report that Chinese MNEs show an unconventional risk-taking behavior choosing foreign locations, where they have no prior experience or there is an increased institutional distance. Drawing on the institutional theory, the purpose of this paper is to argue that Chinese Government officia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 87 publications
(196 reference statements)
2
32
0
Order By: Relevance
“…We measured prior local experience through a dummy variable coded one if the Chinese firm already had subsidiaries in the host country before it established the focal subsidiary, and zero otherwise (Estrin, Baghdasaryan, & Meyer, ; Li et al, ; Nagano, ; Quer, Rienda, & Andreu, ; Quer, Rienda, Andreu, & Miao, ; Slangen, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We measured prior local experience through a dummy variable coded one if the Chinese firm already had subsidiaries in the host country before it established the focal subsidiary, and zero otherwise (Estrin, Baghdasaryan, & Meyer, ; Li et al, ; Nagano, ; Quer, Rienda, & Andreu, ; Quer, Rienda, Andreu, & Miao, ; Slangen, ).…”
Section: Methodsmentioning
confidence: 99%
“…We created a dummy variable equal to one if a Chinese government delegation paid an official visit to the host country in the focal year or in the immediate previous year, and zero otherwise (Quer, Rienda, Andreu, & Miao, ; Voss et al, ). Collecting data from the Ministry of Foreign Affairs of the People's Republic of China website, we included visits by the Chinese President, Prime Minister, Ministers or Vice Ministers of Commerce, Foreign Affairs, Transport, etc., as well as senior officials of other Chinese governmental institutions such as the National People's Congress, the Politburo Standing Committee, and the Chinese People's Political Consultative Conference.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, and at first blush, Chinese approaches to practising uncertainty appear to come with more unconventional risk-taking behaviour. This, however, is accompanied by an understanding of interdependencies of actions, most notably relationship building (Opper et al, 2017 ; Quer et al, 2019 ) while carefully accumulating abroad experience (Liu et al, 2016 ). Extant literature, therefore, suggests flexibility, realism and pragmatism with which Asian organisations handle hard-to-predict and disorientating environments.…”
Section: Research On Shocks In Asiamentioning
confidence: 99%
“…However, other studies show that several mechanisms may influence the choice of a foreign market with high institutional distance. For example, Quer et al (2019) found that Chinese firms enter markets with high institutional distance without having any prior experience, when these countries had been visited by Chinese government officials, indicating that political ties between countries may help overcome institutional distance. From a similar perspective, Kedia and Bilgili (2015) find that historical ties between the home and the host country can reduce institutional distance in terms of market selection.…”
Section: The Role Of Institutional Distance In Ib Decisionsmentioning
confidence: 99%